2019
DOI: 10.1002/jimd.12110
|View full text |Cite
|
Sign up to set email alerts
|

A novel phosphoglucomutase‐deficient mouse model reveals aberrant glycosylation and early embryonic lethality

Abstract: Patients with phosphoglucomutase (PGM1) deficiency, a congenital disorder of glycosylation (CDG) suffer from multiple disease phenotypes. Midline cleft defects are present at birth. Overtime, additional clinical phenotypes, which include severe hypoglycemia, hepatopathy, growth retardation, hormonal deficiencies, hemostatic anomalies, frequently lethal, early‐onset of dilated cardiomyopathy and myopathy emerge, reflecting the central roles of the enzyme in (glycogen) metabolism and glycosylation. To delineate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 26 publications
0
3
2
Order By: Relevance
“…This somehow counterintuitive observation has been reported for other IEM disorders 44,45 . When exploring early lethality annotations in humans, up to 39% of the known biallelic IEM genes have records of lethality before or shortly after birth, showing that a considerable proportion of these conditions in humans are life threatening, leading to early death if untreated.…”
Section: Resultscontrasting
confidence: 52%
See 1 more Smart Citation
“…This somehow counterintuitive observation has been reported for other IEM disorders 44,45 . When exploring early lethality annotations in humans, up to 39% of the known biallelic IEM genes have records of lethality before or shortly after birth, showing that a considerable proportion of these conditions in humans are life threatening, leading to early death if untreated.…”
Section: Resultscontrasting
confidence: 52%
“…In fact, for the four candidate genes highlighted in our study, it is the heterozygous mouse model which is mimicking the phenotypes observed in patients carrying biallelic mutations. This somehow counterintuitive observation has been reported for other IEM disorders 44,45 .…”
Section: Undiagnosed Cases Of Inherited Metabolic Disorders From the 100kgpcontrasting
confidence: 52%
“…Moreover, zinc finger protein 350, acetyl CoA acyltransferase, membrane-associated guanylate kinase, and two members of the DnaJ heat-shock protein family were found to be novel binding proteins of DYRK3. Although PGM1 plays a fundamental role in glycolysis, glycogenesis, and glycogenolysis [ 18 ], both ADAM22 and SNAPIN are closely related to the synaptic transmission of neurotransmitters [ 19 ]. Among these proteins, SNAPIN was chosen as a target of further analysis because some reports demonstrated that proper action of SNAPIN is critical for neuronal homeostasis, which is primarily attributed to the efficient axonal retrograde transport of various molecules via the mitochondria and autophagosome, as well as by precise synaptic neurotransmitter secretion [ 9 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…New techniques such as clustered regularly interspaced short palindromic Repeats (CRISPR)/Cas9 or conditional knockouts [ 42 ] have made in vivo gene engineering more accessible and efficient. In the past five years, several in vivo models have been developed for CDG, allowing the identification of pathophysiologic mechanisms [ 43 , 44 , 45 ] and the pre-clinical testing of drug repositioning candidates [ 46 , 47 ]. A compilation of both in vitro and in vivo disease models reported since October 2017 is presented in Table 2 .…”
Section: Resultsmentioning
confidence: 99%